2014
DOI: 10.1371/journal.pone.0092293
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Distribution Patterns of Host Insects of Caterpillar Fungus Ophiocordyceps sinensis in the Qinghai-Tibet Plateau

Abstract: The caterpillar fungus Ophiocordyceps sinensis is one of the most valuable medicinal fungi in the world, and it requires host insects in family Hepialidae (Lepidoptera) to complete its life cycle. However, the genetic diversity and phylogeographic structures of the host insects remain to be explored. We analyzed the genetic diversity and temporal and spatial distribution patterns of genetic variation of the host insects throughout the O. sinensis distribution. Abundant haplotype and nucleotide diversity mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
0
43
1
Order By: Relevance
“…The origination time estimate of the fungus based on the 5‐locus data set, however, differed from that based on the ITS data set, but was similar to the time estimate of host insects reported by Quan et al . (). Using a slower substitution rate, Quan et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The origination time estimate of the fungus based on the 5‐locus data set, however, differed from that based on the ITS data set, but was similar to the time estimate of host insects reported by Quan et al . (). Using a slower substitution rate, Quan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Using a slower substitution rate, Quan et al . () revealed that host insects first diverged around 4.1 Mya. In the absence of fossil evidence and/or more robust molecular clocks for these two organisms, the above time estimates must be considered tentative.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial intraspecific genetic diversity has been observed in O . sinensis , which may be because of the diversity of terrains and climates on the Tibetan Plateau and the broad insect host range (more than 50 species in the family Hepialidae ) (Quan et al ., ; Zhang et al ., ). The genetic divergence of O .…”
Section: Taxonomy Biology Distribution and Artificial Cultures Of Omentioning
confidence: 99%
“…O . sinensis is widely distributed on Tibetan Plateau and its surrounding regions (Liang et al ., ; Quan et al ., ; Zhang et al ., ). In China, it is commonly called ‘Dong Chong Xia Cao’ (means ‘winter worm summer grass’) and has been used as a medication in China for over 300 years (Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the genetic diversity and the present-day distributions of Calinaga should be attributed not only to the dramatic geological events in Oligocene/Miocene, but also to the impacts of the cycles of glacial advance/retreat that occurred in this region during the Pleistocene (Quan et al 2014).…”
Section: Historical Biogeographymentioning
confidence: 99%